2005
DOI: 10.4018/jebr.2005040101
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Internet-Based Marketing Channels by Small- and Medium-Sized Manufacturers

Abstract: This paper analyses factors influencing manufacturers' adoption of Internet-based marketing channels using models based on marketing channel and organisational innovation theory. Survey data from 1,163 Danish, Finnish, and Swedish manufacturers form the empirical basis for testing the models using LISREL analysis. The results stress that adoption of Internet-based marketing is influenced by willingness to cannibalize, by management support, by market pressure, and by a firm's knowledge of IT. A willingness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…We believe our study is one of the first empirical studies examining the impact of extensiveness of business process digitalization on SME new product development. Previous literature has mostly focused on either the antecedents of BPD or the financial consequences of using one or more specific types of e-business practices, leaving the impact of using an enterprise-wide BPD on product development largely unexplored (e.g., Nielson et al, 2005;Xu et al, 2007). By adopting insights from the knowledge-based view and the organizational learning theory, this study found a linkage between BPD and new product development.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 87%
See 1 more Smart Citation
“…We believe our study is one of the first empirical studies examining the impact of extensiveness of business process digitalization on SME new product development. Previous literature has mostly focused on either the antecedents of BPD or the financial consequences of using one or more specific types of e-business practices, leaving the impact of using an enterprise-wide BPD on product development largely unexplored (e.g., Nielson et al, 2005;Xu et al, 2007). By adopting insights from the knowledge-based view and the organizational learning theory, this study found a linkage between BPD and new product development.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 87%
“…To date, the majority of research on SME's BPD has focused on the antecedents of SMEs engaging in one or few specific types of e-business practice or process (Wymer & Regan, 2005). For example, scholars have examined factors at the organizational level (e.g., Burke, 2005;Dholakia & Kshetri, 2004;Nielson, Host & Mols, 2005;Xu, Rohatgi & Duan, 2007); the industrial level (e.g., Dholakia & Kshetri, 2004;Lee, 2004); and the institutional level (e.g., Kshetri, 2007) that influence the SME's decision to adopt BPD. Less in quantities, studies also have looked at the role of BPD in influencing SMEs' market and operational performance (e.g., Johnston et al, 2007;Merono-Cerdan & Soto-Acosta, 2006;Rajendran & Vivekanandan, 2008;Zhu, Kraemer, Xu & Dedrick, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to perceived benefits and risks, the availability of resources (Cragg & King, 1993;Lee, 2004) and social pressures such as the pressures from clients, suppliers, and competitors (Nielsen, Høst, & Mols, 2005) also contribute to the manufacturer's intention to initiate an ODSC. Therefore, we also propose: Proposition 3: The manufacturer's intention to establish an ODSC will be positively related to the availability of resources required.…”
Section: Prospect Theorymentioning
confidence: 99%
“…Still another challenge to the managers of bricks-and-clicks stores is the cannibalization effect on the sales of their existing physical stores (Grunberg, 1999;Nielson, Host, & Mols, 2005). Online sales may reduce off-line sales, and competition between managers of the two types of commerce within a single retailer may prevent them from cooperating with each other.…”
Section: Challenges To Bricks-and-clicksmentioning
confidence: 99%